The Relation of Public Expenditure in Education and Health on life Expectancy - Touray, Khadijatou; Dokmak, Mahmoud; Sohna, Nasirou (Universitas Bojonegoro, 2025)
This paper assesses the impact of public spending on education and health on life expectancy in five countries: Germany, Japan, India, Brazil, and South Africa, using data from 2010 - 2021 from WDI. The methodology involves descriptive statistics, correlation analysis, regression analysis, and visual representation. The dependent variable is life expectancy, while education and health expenditure (as a percentage of GDP), along with GDP per capita, are the independent variables. Findings show a statistically significant positive relationship between health spending and life expectancy, particularly in high-income countries such as Japan and Germany. However, education spending does not show any meaningful impact across the five countries. Country-specific interactions suggest varying points of efficiency in spending, with South Africa standing out as an outlier, showing high expenditure but poor outcomes, likely due to systemic health burdens. The study concludes that health spending has a more direct and meaningful impact on longevity than education spending within the years of study. Policy recommendations emphasize increasing health investment, improving the efficiency of healthcare delivery, and enhancing education to indirectly support health outcomes. Limitations include sample size and omission of other socio-economic variables such as disease burden, healthcare access, and governance quality.